Effectiveness of Frangipani Leaf Extract (Plumeria alba Linn.) as a UV Filter - Irein Kusuma Angreini; Aniek Prasetyaningsih; Vinsa Cantya Prakasita (BERITA BIOLOGI, 2021)
UV filters are necessary since UV rays are harmful to human skin. UV filter compounds in commercial sunscreen products can cause adverse effects. Thus, natural UV filters containing flavonoids, e.g. Frangipani (Plumeria alba Linn.) leaves, are needed. This research examined the use of flavonoids from P. alba leaf as a UV filter with in vitro and in vivo. Maceration was performed with 70% ethyl alco-hol and liquid-liquid extraction for flavonoid purification. Parameters tested were total flavonoid compounds, SPF value, and clinical symptoms of the melanogenesis inhibition scoring. The purification result was 43.6%. The flavonoid concentration in pure extract (64.4 mg QE /g) was higher than crude extract (57.6 mg QE/g). The highest SPF value (33.88) was observed in pure extract at 1400 mg/mL, while the same concentration of crude extract resulted in a lower SPF value (33.06). Pearson correlation analysis (0.536) indicated a di-rectly proportional relationship between SPF value and extract concentration. In vivo analysis was performed by scoring between 0-4 following the severity of erythema. After 21 days of sunlight exposure, the worst erythema was found in the negative control group (score 1.292). The best result was found in the group treated with pure extract 1400 mg/ml (score 0.542).